STUDENT INVOLVEMENT TOWARDS LECTURER FEEDBACK IN ACADEMIC WRITING: A QUALITATIVE EXPLORATION - Arianty, Nur Jihan; Maman Suryaman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher feedback plays an essential role in helping students develop academic writing skills, yet many students still struggle to engage fully with the feedback they receive. This study aims to explore how students engage with teacher feedback in academic writing classes and to identify factors that influence their engagement. Using a qualitative descriptive design, data were collected through semi-structured interviews, open-ended questionnaires, and documentation of actual teacher feedback. The participants were undergraduate students from the English Education Study Program who had previously taken an academic writing-related course. The findings reveal that students engage with feedback behaviorally by revising drafts step by step, cognitively by analyzing and interpreting comments, and emotionally through feelings of motivation, concern, or appreciation. Students' engagement is strongly influenced by the clarity, specificity, tone, and amount of feedback provided by the lecturer. Clear instructions, supportive language, and concrete examples increase students' motivation and willingness to revise. These findings highlight the importance of structured and accessible feedback to improve students' writing outcomes.